2004
DOI: 10.1093/jn/134.3.586
|View full text |Cite
|
Sign up to set email alerts
|

High-Protein, Low-Fat Diets Are Effective for Weight Loss and Favorably Alter Biomarkers in Healthy Adults

Abstract: Although popular and effective for weight loss, low-carbohydrate, high-protein, high-fat (Atkins) diets have been associated with adverse changes in blood and renal biomarkers. High-protein diets low in fat may represent an equally appealing diet plan but promote a more healthful weight loss. Healthy adults (n = 20) were randomly assigned to 1 of 2 low-fat (<30% energy), energy-restricted groups: high-protein (30% energy) or high-carbohydrate (60% energy); 24-h intakes were strictly controlled during the 6-wk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
137
1
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(154 citation statements)
references
References 32 publications
7
137
1
9
Order By: Relevance
“…Studies with strictly controlled energy intake have shown that weight reduction can be achieved with any dietary regimen as long as energy intake is lower than energy expenditure [21][22][23][24]. Permanently reduced energy intake, which is essential after weight reduction unless energy expenditure by physical activity is clearly increased, is more difficult to achieve [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with strictly controlled energy intake have shown that weight reduction can be achieved with any dietary regimen as long as energy intake is lower than energy expenditure [21][22][23][24]. Permanently reduced energy intake, which is essential after weight reduction unless energy expenditure by physical activity is clearly increased, is more difficult to achieve [25].…”
Section: Discussionmentioning
confidence: 99%
“…Still another popular, and evidently efficient [22,31] weight-loss approach is to increase protein intake up to 30% of total energy, with a decrease in either fat or carbohydrate. An increase in protein intake may increase patient satisfaction during a low-fat, energy-restricted diet [22] and has been shown to accelerate weight loss [33] and prevent weight regain [34]. In our study we emphasised adequate protein intake (0.8 g/1 kg body weight) but did not advise to increase it more than that.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that increased consumption of healthful foods (eg, whole grains/ cereals [45], fruits, vegetables [45], low-fat dairy products [46], and other low-fat foods [47]) is associated with lower mortality rates from obesity and related metabolic diseases (45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true given the recent popularity of high protein diets in weight management [16]. Although the efficacy of these diets with regard to weight loss is still subject to debate, several studies have demonstrated favorable physiological effects [12,[16][17][18][19][20][21][22][23][24]. This has led to a substantial increase in protein intake by individuals adhering to contemporary weight loss plans.…”
Section: Dietary Protein Intake and Renal Functionmentioning
confidence: 99%
“…Although the efficacy of high protein diets for weight loss has been evaluated, there have been no reports of proteininduced diminutions in renal function despite subject populations that are generally at risk for kidney disease (e.g., dyslipidemia, obesity, hypertension) [14,15,22,[85][86][87]. A randomized comparison of the effects of high and low protein diets on renal function in obese individuals suggested that high protein diets did not present a health concern with regard to renal function their study population [65].…”
Section: Evidence In Healthy Individualsmentioning
confidence: 99%